Perbedaan Penyuluhan Menggunakan Media Video Animasi dan Booklet Terhadap Pengetahuan Cara Menyikat Gigi Pada Murid Sekolah Dasar Kelas IV Dan V SDN Pulang Pisau 5 Kabupaten Pulang Pisau - Nesia Septiani, Utari; Kisworo Utami , Naning; Fansurna, Anderi; Bunga Nurwati (Poltekkes Kemenkes Banjarmasin, 2024)
Dental and oral health problems are the most common problems in children. The 2022 screening data on the dental health of school children in the Pulang Pisau Health Center working area at SDN Pulang Pisau 5, obtained a percentage of caries 94.10%. This research aims to find out the differences before and after Counseling Using Animated Video Media and Booklets on the Knowledge of How to Brush Your Teeth in Grade IV and V Elementary School Students of Pulang Pisau 5. Type of research used is a pseudo-experiment (quasi eksperiment) using the statistical test of the T-Test Paired Sample Test and Independent T-test. From the results of knowledge research using animated video media in grade IV and V students of SDN Pulang Pisau 5 Pulang Pisau Regency got a good category of 87.1%, and knowledge after counseling with booklet media got a good category of 74.2%. The test results carried out after extension using animated video media and booklets obtained a value of ρ= 0.175 this value showed greater than α= 0.050. There is no level of difference in knowledge on how to brush your teeth after counseling with animated video media and booklets